التنبؤ بمرض السكري بإستخدام طُرق التعلم العميق - فلاح مروة (university of eloued جامعة الوادي, 2024)
أثبتت الدراسات الحديثة أن مرض السُكري هو المرض المُزمن الأكثر إنتشارًا، بحيث يتزايد عدد الأشخاص المصابين بهذا المرض بشكل كبير في جميع أنحاء العالم. الكشف المبكر لمرض السكري مُهم جدًا لعلاجه في الوقت المناسب. مؤخرًا أصبح الكشف عن المرض بالطُرق التقليدية معقدًا للغاية بالنسبة للخبراء البشريين (الطبيب، المُمرض). ولهذا السبب، من الضروري وجود نظام آلي للتنبؤ الدقيق والفعال لمرض السكري. في الآونة الأخيرة ، أثبتت طرق التعلم الآلي والتعلم العميق بصفة خاصة دورها الكبير في مختلف المجالات، من بينها الطب والرعاية الصحية، النقل، التعليم، الأمن، التنبؤ بالكوارث والأمراض وغيرها. من خلال الدراسات الحديثة، نجد أن طرق التعلم العميق حققت نسب نجاح عالية جدًا في الكشف والتنبؤ بمختلف الأمراض مثل تحديد الإصابة بمرض السرطان، مرض القلب، مرض السكر ،الزهايمر،...إلخ، وذلك من خلال مؤشرات المرض وخصائصه. في هذه الدراسة قُمنا بتطوير نظام من أجل التنبؤ بمرض السُكري بإستخدام طرق التعلم العميق، حيث أننا إخترنا نموذج من نماذج التعلم العميق DNN، ثم قُمنا بتدریبه وتقییمه بإستخدام مجموعة كبيرة من البيانات، كما أننا تحققنا من آداء النموذج المُقترح مُقارنة بطرق التعلم الآلي الأكثر إستخدامًا، فأظهرت التجارب المكثفة أن اقتراحنا يمكن أن يحسن الأداء بشكل ملحوظ. The current studies confirm that diabetes is one of the most widespread chronic diseases, as the number of people infected with it is increasing rapidly worldwide. Early diagnosis of diabetes is crucial for timely treatment. lately, detecting the disease has become too complex for experts (doctors and nurses). Therefore, having an automated system for accurate and effective diabetes prediction is necessary. Recently, automated learning methods, particularly deep learning, have demonstrated their significant role in various fields, including medicine, healthcare, transportation, education, security, disaster forecasting, and disease prediction, among others. Through these studies, we found that deep learning methods have achieved high success rates in detecting and predicting various diseases, such as cancer, heart disease, diabetes, Alzheimer’s, etc., using disease indicators and characteristics. In this study, we developed a system to predict diabetes using deep learning methods. We selected the DNN model, trained and evaluated it using a large dataset. We also verified the performance of the combined model by comparing it to commonly used machine learning methods. Extensive experiments showed that our proposal can significantly improve performance.
مدكرة ليسانس اعلام الي
Keywords: مرض السُكري، الكشف عن المرض، التعلم العميق، التعلم الآلي، الذكاء الإصطناعي، التنبؤ بمرض السكري; الشبكات العصبية. فرنسيــة او إنجليزية:Diabetes; disease detection; deep learning; machine learning; artificial intelligence; prediction of diabetes; Artificial neural network.